Jamaican teachers, Jamaican schools : life and work in 21st century schools - Blair, Eleanor (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2023)
"Nowhere is teachers' lives and work more challenging than in Jamaican schools. Teachers in Jamaica are regularly faced with limited resources and challenging students. Teacher pay has been historically low and current conditions continue a long tradition of providing minimal compensation for teachers' work. Recent school reform efforts has been successful in producing a teaching force that is better educated than ever before, and yet, teachers are seldom given the autonomy in decision-making and/or respect that accompanies the work of comparable professions. Coupled with these issues, teachers regularly face hunger, poverty, behavioral issues and a lack of parental support as part and parcel of their experience in 21st century schools. If teachers are perceived as having low professional status, it is not surprising that they are often blamed for the shortcomings of Jamaican schools. The citizens of Jamaica are firmly committed to the notion that "every child can learn, every child must learn;" however, the reality is that while all children can learn, many children do not learn in this country where the allocation of resources favors the rich and disowns the poor. Public schools in Jamaica vary tremendously across the fourteen parishes. Geography and social class regularly determine both the context and circumstances of teachers' work, and yet, discussions of teachers seldom acknowledge the differences. There is a place for a more in-depth examination of teachers' work and teachers' lives in Jamaica where a consideration of the emergence of teacher leadership and higher professional status can intersect with a vision of new roles and responsibilities for teachers. While many of the reports on Jamaican education consider the role of administrative leaders, there is an absence of any discussion of the role of teacher leaders is school reform. It is interesting that a country can advocate for higher levels of teacher preparation and an upgrading of the professional status of teachers, and yet, ignore the potential power of teachers as major actors directing efforts to reform the schools. Teachers acting as leaders, in a profession dominated by women, would challenge the status quo and usurp preconceived notions regarding the work of teachers. In this book, 21st century descriptions of teachers' lives and work will accompany a consideration of how the transformation of the teaching profession could positively impact both schools and classrooms across the island"--